Scutellaria jishouensis (Lamiaceae), a new species from Hunan, China - Tan, Lu; Xiang, Xiao-Mei; Liu, Bing; Wang, Zhi-Cheng; Zhang, Dai-Gui; Chen, Gong-Xi (Phytotaxa, 2022)
A new species of Scutellaria (Lamiaceae), Scutellaria jishouensis G. X. Chen, L. Tan & X. M. Xiang, sp. nov from Dehang Scenic Spot, Hunan Province of China, is described and illustrated. Scutellaria jishouensis is morphologically similar to S. indica and S. calcarata, but can be easily distinguished by its creeping, spreading to erect or ascending-erect, stem with forked adventitious roots; leaves membranous, sparsely crenate or entire; racemes 1-10 cm, corolla sparsely pilose or glabrous on adaxial, glabrous inside, and flowering and fruiting in late April-June. Phylogenetic analyses, based on the nuclear ribosomal internal and external transcribed spacers, showed that S. jishouensis and S. calcarata were sister species with good support. The results of both morphological data and the phylogenetic analysis support the specific rank of S. jishouensis.